RESISTANCE PATTERN OF Escherichia Coli AGAINTS ANTIBIOTICS IN URINARY TRACT INFECTION PATIENTS IN RSUD DR. SOETOMO SURABAYA - Ariana, Novi; Pestariati, Pestariati; Sasongkowati, Retno; Kusumaningrum, Debby (Universitas Airlangga, 2020)
Pathogenic bacteria cause Urinary Infection imore or lessi about 85 - 95% are bacteria Escherichia coli. The treatment of Urinary Tract Infection (UTI) requires adequate supportive therapy and antibiotics, but antibiotic resistance is an obstacle in UTI treatment. This study aims to determine the types of antibiotics that are resistant to Escherichia coli in patients with UTI. This is an observational study with a descriptive method to determine the type of antibiotic-resistant to Escherichia coli in patients with UTI in the Laboratory of Clinical Microbiology RSUD Dr. Soetomo. Antibiotics that were resistant to Escherichia coli in UTI patients were cefazolin (80.49%), Amoxicillin Clavulanic Acid (73.17%), Ampicillin (73.17%), Tetracycline (68.29%), while antibiotics that were resistant to Escherichia coli ESBL was Amoxicillin Clavulanic Acid (100%), Ampicillin (100%), Cefazolin (99.7%), Aztreonam (99.7%), Ceftazidime (99.7%). The prevalence of Escherichia coli in UTI patients was 27.5%, while Escherichia coli ESBL was 72.5%. Based on the results of the research that has been obtained, it is better to do research on antibiotic resistance patterns periodically.